Doppler Flow Velocity Indices (RI, PI, S/D & PSV) of Fetal Middle Cerebral Artery in Normal Pregnancies: Correlation with Gestational Age of 20 to 40 Weeks - Taher, Md Abu; Tasmin, Nuzhat; Mohiuddin, AS; Ul Alam, Md Mohit; Sharif, Md Mofazzal; Ghos, Kona (BIRDEM Medical Journal, 2012)
This observational type of descriptive study was carried out in the Department of Radiology and Imaging, BIRDEM selecting 70 Bangladeshi pregnant babies with the aim to find out the normogram of foetal middle cerebral artery Doppler flow velocity indices and correlation between Doppler flow velocity indices [Resistance Index (RI), Pulsatility Index (PI), Systolic/Diastolic ratio (S/D) & Peak Systolic Velocity (PSV)] of foetal middle cerebral artery and gestational age in normal pregnancies of 20 to 40 weeks. It was observed that RI, PI and S/D were decreased with the advance of gestational age but PSV was increases with the advance of gestational age. Statistical analyses showed there were significant difference between mean PSV, RI and PI before and after 25 weeks of gestation. No significant difference was found between mean S/D before and after 25 weeks of gestation. It was observed from Correlation analysis between Doppler indices with independent gestational age that all the Doppler indices of foetal middle cerebra artery was positively correlated with the whole gestation period. The statistical analysis showed only PSV and RI were significantly correlated with the gestational age. Simple regression analysis between dependent Doppler index with independent gestational age before and after 25 weeks revealed that all the Doppler indices had positive relationship with the corresponding gestational age but relationship between PSV and PI (before 25 weeks) with their corresponding gestational ages were only statistically significant. DOI: http://dx.doi.org/10.3329/birdem.v2i2.12306 Birdem Med J 2012; 2(2) 77-80